THE IMPRESSION OF WORK STRESS ON EMPLOYEE PRODUCTIVITY POST-PANDEMIC AT THE MARDIWALUYO CLINIC IN GUNUNG PASIR SEKAMPUNG UDIK, EAST LAMPUNG) - Hikmatul Aliyah; Miswan Gumanti; Susi Sulastri; Hendi Darma (Journal of Research in Social Science and Humanities, 2025)
Job stress is a condition where an individual experiences physical and psychological imbalance that can affect emotions, thoughts, and individual conditions due to large work demands. Efficiency is a measure in comparing planned input with actual input. Does the Impression of Job Stress Affect Employee Productivity Post-Pandemic at the Mardi Waluyo Clinic, Gunung Pasir Jaya, Sekampung Udik, East Lampung? This study aims to determine the effect of the Impression of Job Stress on Employee Productivity Post-Pandemic at the Mardi Waluyo Clinic, Gunung Pasir Jaya, Sekampung Udik, East Lampung. This study employed a descriptive quantitative method. Data collection was conducted using a questionnaire, with 28 respondents using a saturated sampling technique. The data analysis technique used was simple regression with SPSS 16. The results of this study indicate that the variable of impression of work stress has a positive and significant influence on the work productivity of Mardi Waluyo Gunung Pasir Clinic employees. The correlation coefficient value is 75.4%, while the remaining 23.6% is influenced by other factors not included in this study.